Sintesis dan Karakterisasi TiO2/Zn Dengan Metode Yang Ramah Lingkungan - Rahimmah, Nur; Suryani, Okta (Departemen Kimia FMIPA UNP, 2024)
The increasing use of fossil fuels leads to increased carbon emissions from the combustion process of fossil fuels. Therefore, sustainable and environmentally friendly alternative energy sources are needed as a substitute for fossil fuels. Hydrogen is one of the potential substitutes for fossil fuels because it has the highest energy density and is environmentally friendly. Hydrogen can be produced through photochemical water splitting by utilizing solar energy and abundant water resources. Hydrogen production through photochemical water splitting in the process uses TiO2 semiconductor material as a photocatalyst. This research has been synthesized and characterized TiO2 and TiO2 photocatalysts doped with Zn metal to reduce the band gap. TiO2 has an anatase crystal structure with an average particle size of 27,07 nm. TiO2 band gap is 3,27 eV. Then doping with Zn metal and causes the band gap energy to decrease to 3,20 eV. Metal doping is proven to reduce the band gap energy of TiO2 semiconductor photocatalyst.